THE STUDY OF THE IMPORTANCE OF LESSON PLANNING AND ORGANISING IN TEACHING EFL - Umaraliyeva Munojatxon; Sobirova Odina Jaxongirovna; Orifjonova Durdona (Лучшие интеллектуальные исследования, 2024)
In the present article, the researcher aims to identify the relationship between lesson plans and classroom management and attempt to determine the effect of English teachers’ lesson preparation on the implementation of those lessons. Further, we seek to explore English teachers’ perceptions toward the role of lesson planning in classroom management in English as a first language (EFL) classroom. We English teachers in secondary schools in via electronic questionnaire, and our findings demonstrate the importance of lesson planning in classroom management, revealing that English teachers prepare their lessons effectively to sufficiently manage classrooms. In addition, our results indicate that lesson planning is an essential skill that English teachers must cultivate to create a successful classroom environment. Moreover, the outcomes of the present study highlight most English teachers’ attitudes toward the role of lesson planning in classroom management are positive. Finally, we find a significant and positive relationship between effective lesson preparation and teachers’ abilities to create a successful EFL classroom environment.